Análisis socioespacial de la gentrificación: La llegada del concepto al sur global y sus implicancias - Gonzales-Malca, Gabriela (2020)
The essay proposes a brief analysis of the emergence of the concept of gentrification and its 'assimilation' in the global south. For this, the importance of the socio-spatial approach as a tool for analyzing the link between the city and those who inhabit it is highlighted. The Anglo-Saxon origin of the concept, which supposes a contextualization to understand it from and in Latin urban contexts, makes interdisciplinary reflection necessary to understand the complexity of the process. In the same way, the conceptual approach of the essay is complemented by the territorial processes and dynamics registered in Latin cities. Some emblematic examples will be taken to help stage how the gentrification process occurs in these spaces. Finally, topics are proposed that can contribute to the discussion, concluding with some alternatives to the problems that arise from the phenomenon of gentrification.